Pilot study on process evaluation of DHLS program conducted through real Vis-à-Vis virtual modes: 2007-08 - Basavaraj, Vijayalakshmi; S, Venkatesan; M S, Vasanthalakshmi; P, Purusotham (Journal of All India Institute of Speech and Hearing, 2010)
Distance Learning (DL) is a system and process for providing instruction from a distance. This is distinguished from real or traditional instruction, in which all students are on campus face-toface with the instructor. There are several misconceptions and misapprehensions regarding DL-especially regarding its newer formats by use of two way live and interactive teleconference modes, use of virtual classrooms and/or such other technology enabled services for teaching and education. The DHLS (Diploma in Hearing, Language and Speech) program initiated at AIISH, Mysore (2007-08) through terrestrial linked two way video-conference mode in 11 centers across the country offers a splendid occasion and opportunity to undertake a comparative process evaluation through real vis-à-vis virtual modes of instruction. By combining the use of a cross sectional multi-group comparison design along with a component of survey and tool development embedded within it, the present study seeks to evaluate interpersonal perceptions between teacher-pupil, their vies on the technology enabled methods of instruction as well as their impact in terms of comparative performance and results in the end annual examination of the students by using appropriate and standardized questionnaires, rating scales and self reporting schedules. Results indicate highly satisfactory mutual ratings both by teacher/ supervisors as well as students across real and virtual centers. In terms of the findings on evaluation of the video-conferencing, teachers experience greater problems or glitches related to the use of this technology than the recipient students. Finally, there appears to be no differences in the eventual outcome of results in final examinations between the two modes of distance learning in the field of communication disorders. The implications of the study along with future potential and possibilities for research along these lines are presented and discussed.